Effect of Vibration-Assisted Butt Welding on Tensile Strength of Welded Joints: An Experimental Study - Yusuf Rizal Fauzi; Ismail Ramli; Halman (Asian Journal of Mechanical Engineering, 2025)
Vibration-assisted welding has emerged as a promising technique for improving weld quality and mechanical performance without modifying conventional welding parameters. In this experimental study, the effect of low-frequency vibration-assisted butt welding on the tensile strength of mild steel welded joints was investigated. Shielded Metal Arc Welding (SMAW) was employed to fabricate butt joints under different welding currents, vibration durations, and vibration frequencies, while maintaining consistent welding conditions. Tensile tests were conducted in accordance with ASTM E8 standards, and the corresponding microstructural characteristics of the weld zone were examined using scanning electron microscopy.The results revealed that welded joints produced with vibration assistance exhibited consistently higher tensile strength compared to non-vibrated specimens. The maximum tensile strength improvement of approximately 6% was observed in specimens subjected to higher vibration frequency and longer vibration duration. Microstructural analysis showed that vibration-assisted welding promoted grain refinement and improved microstructural homogeneity, while non-vibrated welds displayed coarser and non-uniform grain structures. The refined microstructure reduced defect formation and enhanced resistance to crack initiation, leading to improved tensile performance. The study demonstrates that low-frequency vibration-assisted butt welding effectively enhances the tensile strength of welded joints by modifying weld pool dynamics and solidification behavior. The findings highlight the practical potential of vibration-assisted welding as a simple and efficient method for improving joint strength and structural reliability in welded components.